2021
DOI: 10.3390/biomedicines9101350
|View full text |Cite
|
Sign up to set email alerts
|

Live Birth Rates after Active Immunization with Partner Lymphocytes

Abstract: Although many potential causes have been established for recurrent implantation failure (RIF) and recurrent miscarriage (RM), about 50% of these remain idiopathic. Scientific research is focused on immunological risk factors. In the present study, we aim to evaluate live birth rates after immunization with paternal lymphocytes (lymphocyte immunotherapy (LIT)). This retrospective study consisted of 148 couples with a history of RM and/or RIF. The women underwent immunization with lymphocytes of their respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…Unfortunately, we did not have the information about the number of pregnancy attempts and embryo transfers before and after LIT, mainly because patients were assigned by many fertility centers from all over Germany. In future studies this information needs to be taken into account, especially since it was shown that LIT is more successful in patients with a history of recurrent miscarriages than with recurrent implantation failure 48 . This study was neither randomized nor controlled.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Unfortunately, we did not have the information about the number of pregnancy attempts and embryo transfers before and after LIT, mainly because patients were assigned by many fertility centers from all over Germany. In future studies this information needs to be taken into account, especially since it was shown that LIT is more successful in patients with a history of recurrent miscarriages than with recurrent implantation failure 48 . This study was neither randomized nor controlled.…”
Section: Discussionmentioning
confidence: 96%
“…The birth rate was 38% after IVF and 42% spontaneously. In a recently published study by Günther et al a live birth rate of 43% was found in 148 couples according to LIT 48 . Interestingly, the success was strongly dependent on the indication: the live birth rate was significantly higher in women with recurrent miscarriages (53%) in contrast to women with recurrent implantation failure (33%), especially in the first 90 days after LIT, which suggest that LIT appears to have a more pronounced effect on women with recurrent miscarriages.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…[ 1 ] It is a multifactorial disorder where various abnormal conditions intertwine together making the phenotype adverse. Previous studies have reported that RM is caused by various factors like genetics, metabolic and hormonal disorders, lifestyle issues, thrombophilia, autoimmunity, uterine anomalies, antiphospholipid syndrome, infection and sperm quality,[ 2 3 4 5 ] but there are no definitive conclusions for the aetiology of 50% of the RM cases. [ 6 7 ]…”
Section: Introductionmentioning
confidence: 99%